An Epidemiological Retrospective Study of Autopsied Dry Thermal Burn - Pandey, Surendra Kumar; Kumar, Awdhesh (Journal of Indian Academy of Forensic Medicine, 2015)
The present retrospective study has been conducted for the period of 5years i.e. 2009 to 2013  based on autopsy of the unnatural death cases resulting from burn. During study period out of total 10215  unnatural Death cases death due to burn injuries was 1911. These cases brought to the Department of  Forensic Medicine, IMS, BHU, Varanasi. Thermal burn injuries were averaging 18.65%. Female burn  deaths dominated over male in the ratio of 3.52:1. Predominant age group found to be 21-30 years  (48.72%) followed by age group 11-20 (23.11%). Most of the deceased were from the married group  (63%) followed by unmarried (15%). Manner of burn death was unknown in most of the cases (96.86%)  followed by accidental burn deaths (2.98%) suicidal (0.1%) and homicidal (.05%). Involvement of rural  population is more 92.78% than urban population (6.49%). Religion wise Hindu (96.70%) predominated  over other religions.
Keywords: Unnatural death; Dowry death; Burn injuries; Executive Magistrate